Angiogenesis modulatory factors in subjects with chronic ocular complications of Sulfur Mustard exposure: A case-control study - Heidary, Fatemeh; Gharebaghi, Reza; Ghasemi, Hassan; Mahdavi, Mohammad Reza Vaez; Ghaffarpour, Sara; Naghizadeh, Mohammad Mehdi; Ghazanfari, Tooba (International immunopharmacology, 2019)
Chronic ocular complications of Sulfur Mustard (SM) exposure leads to severe ocular morbidity during time. The aim of this study was to compare serum levels of Interleukin 17 (IL-17), IL-12, vascular endothelial growth factor (VEGF)-C, VEGF-D and nitric oxide (NO) in SM-exposed patients versus the control group and to measure tear concentration of VEGF-C only in the SM-exposed group. In this prospective case control, 128 SM-exposed patients and 31 healthy control subjects were included. In the case group ocular manifestations were classified to three subgroups of mild (19 cases), moderate (31 cases) and severe (78 cases) forms of disease. Serum levels of IL-17, IL-12, NO, VEGF-C and VEGF-D, in all subjects and tear concentration of VEGF-C in SM-exposed group was evaluated. All subjects were male and mean ± standard deviation (SD) of age in the case and control groups were 44.9 ± 8.8 and 40.9 ± 10.1 years, respectively. Except for significantly lower serum level of IL-17 (p < 0.001) and NO (p = 0.003), other values were not significantly different. The tear concentration of VEGF-C and serum level of IL-12 were not different between subgroups in the SM-exposed group, yet were significantly lower among those with abnormally dilated and tortuous conjunctival vessels and corneal pannus, respectively (p = 0.01, p = 0.015). Exposure to SM significantly reduced serum level of IL-17 and NO in the delayed phase, yet did not influence VEGF-C; VEGF-D or IL-12. •IL-17, IL-12, and are the possible angiogenesis modulators.•Vascular Endothelial Growth Factor-C (VEGF-C) and VEGF-D are stimulators of angiogenesis and lymphangiogenesis.•Serum level of IL-17 and NO reduced significantly in the delayed phase of SM-exposure, yet did not VEGF-C, VEGF-D or IL-12.•IL-17, IL-12, VEGF-C, VEGF-D and NO were not significantly different between the three subgroups of the Case group.•No significant correlation between IL-12 and NO with all VEGF subtypes in SM-exposed group.